Policy Nook — Policy Note: making water pivotal in the design of food systems - Hellegers, P.; Schmitter, Petra S.; Talbi, A.; van Iwaarden, C. (World Scientific Publishing, 2025)
Water plays a crucial role in our food systems and food security. However, the essential role of water for a functioning food system and the impacts of food systems on water availability and quality have not yet been adequately recognized. Due to a lack of coordination among water and food systems actors, there are siloed water, food security, and nutrition strategies. This paper presents the case to make water pivotal in designing food systems, laying out action perspectives for different actors to move toward what we call “water-responsible food systems”. This paper is based on input from many participants during workshops and existing literature. A food systems approach provides an excellent entry point to link food with water considering climate change and energy. Moreover, collective and cross-cutting actions between actors in food systems are essential to make decisive progress, as well as a common language and insight into the trade-offs of the multiple values of water for a clear prioritization of water use and allocation.